Analysis of The Influence of Parents On Reading Interest of Fifth Grade Students In Bonang District Demak Regency - Nur Lailatus Sa’adah; Sukirman; Achmad Hilal Madjdi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Abstract.This study aims to analyze the role of parents in reading interest of students. This research is a type of quantitative research with the number of respondents in the study of 99 fifth grade students at SD Negeri Gugus Sultan Fatah, Bonang District, Demak Regency. The method in this study is quasi experimental This study also used a non-experimental or ex post facto design. The data collection techniques used were questionnaires and documentation. Test instrument using validation test and reliability test. The results of the study is parents influenced the reading interest of fifth grade students in SD Negeri Gugus Sultan Fatah, Bonang District, Demak Regency by 312 or 31.2% and the correlation value was 0, 559. Parents' suggestions should maximize the role to foster students' interest in reading. Children will learn from their parents, so set a good example, where when children see their parents so enjoy reading and judging books can be a great inspiration, of course their reading interest can increase Keywords: role of parents, interest in reading